Numerical analysis of the rheological behaviors of basalt fiber reinforced asphalt mortar using ABAQUS. (30th December 2017) - Zhang, Xiaoyuan; Gu, Xingyu; Lv, Junxiu; Zhu, Zongkai; Zou, Xiaoyong
Highlights: A 3D model composed of directional fiber and mortar matrix is established and simulated in ABAQUS. The additives of fiber into asphalt mortar can cause stress redistribution for mortar matrix. Fiber content has a more remarkable influence on the parameters for Burgers model than its modulus. Abstract: This study aims to investigate the rheological behaviors of basalt fiber (BF) reinforced in asphalt mortar. The samples of basalt fiber asphalt mortar (BFAM) at various BF contents were prepared and were then submitted for the compressive creep test (CCT) and bending creep test (BCT) at high and low temperatures, respectively. In addition, the numerical simulation in finite element ABAQUS software was performed to model CCT and BCT, where the internal structure of the fiber-reinforced materials was considered to build a two-phase composite material model (fiber and mortar matrix) and further analyze the influence of BF on the rheological behaviors. Testing results indicate that BFAM has an excellent reinforcement performance compared with the control sample (0% fiber content). Moreover, numerical analyses show that the addition of fiber into asphalt mortar causes stress redistribution in BFAM and decreases the average stress value of the mortar matrix. The creep results of the three-dimensional numerical simulation using Burgers constitutive model for BFAM exhibit excellent agreement with those of the testing.